ACTIVIDAD LÚDICA Y RENDIMIENTO ACADÉMICO EN LOS ESTUDIANTES DE LA “UNIDAD EDUCATIVA 11 DE NOVIEMBRE” RIOBAMBA-CHIMBORAZO, PERÍODO MARZO –JULIO 2018 - Pogo Torres, Paulina Fernanda (2019)
The purpose of this research project was to determine the influence of parental socialization on the academic performance of Sixth Grade children in Basic General Education of the bilingual intercultural bilingual education unit "Monseñor Leónidas Proaño". Theoretically, each one was described the variables, taking into account that socialization is a process by which a sense of personal identity is obtained of who they are and where they belong and academic performance is a "level of knowledge demonstrated in an area or subject compared with the age norm and academic level the information acquired was based on the research of books, electronic journals among others, methodologically its approach was qualitative, with a non-experimental design; by type it was field, descriptive, correlational, transversal and basic, the population comprised 36 students of sixth grade of basic education its sampling was not probabilistic and intentional when working with 100% of the population, the psychometric test techniques and the concentrate of the qualifications, the cumulative registration instruments, ESPA 29 and the report cards, giving way to the analysis and interpretation of the results obtained in order to reach the conclusions that no measures have been taken to improve the family environment surrounding the children and girls and thus improve the school performance of Sixth A Degree of Basic General Education of the Intercultural Bilingual Fiscal Education Unit "Monseñor Leónidas Proaño".